Importância dos sistemas agroflorestais para agricultura familiar na Amazônia Brasileira: um estudo de caso sobre o Projeto Reca - Croda, Jéssica Puhl (2019)
Agroforestry Systems (SAF) can be seen as an alternative of sustainable production coupled with environmental conservation, which provide environmental, social and economic benefits. With the increasing pressure of agribusiness causing the destruction of the Amazon Forest, strengthening agroecological practices is essential for the maintenance of standing forest. Therefore, the present study has the general objective of evaluating the importance of agroforestry systems for family agriculture, when analyzing the social, ecological and economic influence for income generation and socio-biodiversity valorization as a method of restoration method and productive system in the Amazon. The study was conducted between January 2017 and January 2018 in six agroforestry systems of family farmers of the RECA Project, located in the Lower Green branch, in the district of Nova Califórnia, Rondônia. SAF 1 (28 years), SAF 2 (10 years), SAF 3 and 4 (4 years) and SAF 5 and 6 (1 year). Semi-structured interviews were conducted with the farming families to understand the social function of the SAF, focusing on the reasons for adopting this system. To analyze the ecological function, soil chemical analyzes were carried out, which consisted of soil organic matter (MOS), pH in water, potassium (K), calcium (Ca), magnesium (Mg), phosphorus P) and aluminum (Al). The effective cation exchange capacity (CTC), potential acidity (H+Al), aluminum saturation (m%) and base saturation (V%) were determined. The litter layer was evaluated by Tukey Test at 5% probability, and soil cover according to the Braun-Blanquet visual scale. Shannon diversity indexes, Pielou equability, floristic similarity by Jaccard index, and correlation analyzes between SAF and soil chemical attributes, soil cover, litter thickness, and floristic attributes were determined using Pearson's correlation and canonical correspondence analysis (CCA). The financial evaluation of the oldest SAF (SAF 1 and 2) was performed using the financial indicators: NPV (Net Present Value), Internal Rate of Return (RIR), B/C Ratio (Benefit / Cost), Discounted Payback time of capital recovery) and VAE (annual equivalent value) with an interest rate of 2.5% a.a. The SAF represent the main source of income for the families interviewed and the main motivation for agroforestry adoption was to develop a production system capable of generating income and reforest deforested areas. The fruit tree species are predominant and Theobroma grandiflorum (Willd. Ex Spreng.) Schum., Is the chief carriage of the SAF studied. Over the years, SAFs have been diversified and their main purpose is family feeding (60%). Regarding the floristic attributes, SAF 3 presented the highest diversity and equability indexes among SAF studied, the lowest diversity values were found in SAF 1 and equability in SAF 4, and there was no high similarity among the SAF. In relation to the chemical attributes of the soil, the soils of the study areas are acidic, with low natural fertility, mainly macronutrients. Correlations between SAF and soil chemical attributes, litter thickness, soil cover and floristic attributes, showed significant correlations (p <0.05) and all were considered very strong (r≥0.7) according to Pearson's correlation. The SAF with organic management had a higher percentage of soil cover (87.5%) and higher litter thickness. In the financial evaluation, the SAF were economically viable with positive NPV for the two SAFs analyzed, R $ 55.916,87 (SAF1) and R $ 57.826,16 (SAF2). The different ages of the SAF studied interfere with SOM and accumulation of nutrients. The main difference in relation to the time of SAF may be the content of phosphorus (P2O5) in SAF 1 (28 years). The management time without soil rotation, nutrient pumping and nutrient cycling by leaf fall (or pruning) and maintenance of cultural residues on the surface may have influenced a possible improvement in nutrient value. Already newer SAFs (SAF 5 and 6) presented high levels of Al, H + Al and m in the soil. The management carried out in the areas can exert a great influence on the availability of nutrients to the soil and management techniques such as the use of cover crops and pruning, can allow the improvement in soil quality maintenance.